Ocorrência e patogenicidade de espécies de Fusarium em colmos de milho - Ciliato, Mônica Lúcia (2012)
Fusarium stalk rot is a major disease of maize (Zea mays) in Brazil. The disease is caused by a complex of several fungal pathogens, among them are included several toxicogenic Fusarium species. The objectives of this work were: (i) to identify Fusarium species associated with maize symptomatic and asymptomatic maize stalks collected in maize fields with stalk in the Maringá and Ponta Grossa counties, in Paraná State, and in Rio Verde County, Goiás State; (ii) to characterize the F. graminearum (Fg complex) isolates for the presence of genes involved in the synthesis of trichothecene mycotoxins 3-acetyldesoxinivalenol (3-ADON), 15-acetyldesoxinivalenol (15-ADON), and nivalenol (NIV), using multiplex PCR; and (iii) to investigate the pathogenicity of F. verticillioides (Fver), F. graminearum sensu stricto genotype 15-ADON (Fgss-15-ADON), and F. meridionale genotype NIV (Fmer-NIV) on corn stalks, with inoculation at 30 and 60 days after sowing. This study analyzed 342 single spore isolates of Fusarium. PCR assays with species-specific primers were used for identification of F. verticillioides (Fver), F. subglutinans (Fsub), F. proliferatum (Fpro), and the F. graminaerum complex (Fg complex). The Fg complex was dominant (≥ 89%) over Fver, Fsub, and Fpro among the samples from Paraná State; however, Fver was the dominant species among samples from Rio Verde, Goiás. Trichothecene genotypes in F. graminearum isolates were 96.0% NIV, 3.4 15-ADON, and 0.6% 3-ADON. The last two genotypes were found only Parana State. The pathogenicity tests on two maize hybrids showed that Fver, Fgss-15-ADON, and Fmer-NIV were equally pathogenic to maize when inoculated at 60 days after sowing, and induced a same pattern of necrosis on corn stalks.